Early Onset and Differential Temporospatial Expression of Melanopsin Isoforms in the Developing Chicken Retina - Verra, Daniela Mariana (2011)
PURPOSE. Retinal ganglion cells (RGCs) expressing the photopigment melanopsin (Opn4) display intrinsic photosensitivity. In this study, the presence of nonvisual phototransduction cascade components in the developing chicken retina and primary RGCs cultures was investigated, focusing on the two Opn4 genes: the Xenopus (Opn4x) and the mammalian (Opn4m) orthologs. METHODS. Retinas were dissected at different embryonic (E) and postnatal (P) days, and primary RGC cultures were obtained at E8 and kept for 1 hour to 5 days. Samples were processed for RT-PCR and immunochemistry. RESULTS. Embryonic retinas expressed the master eye gene Pax6, the prospective RGC speciﬁcation gene Brn3, and components of the nonvisual phototransduction cascade, such as Opn4m and the G protein q (Gq) mRNAs at very early stages (E4 ?E5). By contrast, expression of photoreceptor cell markers (CRX, red-opsin, rhodopsin, and -transducin) was observed from E7 to E12. Opn4m protein was visualized in the whole retina as early as E4 and remained elevated from E6 to the postnatal days, whereas Opn4x was weakly detected at E8 and highly expressed after E11. RGC cultures expressed Gq mRNA, as well as both Opn4 mRNAs and proteins. Opn4m was restricted exclusively to the GC layer at all ages, whereas Opn4x was limited to the forming GC layer and optic nerve at E8, but by E15, its expression was mostly in Prox1() horizontal cells. CONCLUSIONS. The early expression onset of nonvisual phototransduction molecules could confer premature photosensitivity to RGCs, while the appearance of Opn4x expression in horizontal cells suggests the identiﬁcation of a novel type of photosensitive cell in birds.